2009
DOI: 10.1002/bem.20535
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields stimulation affects BMD and local factor production of rats with disuse osteoporosis

Abstract: Pulsed electromagnetic fields (PEMF) have been used widely to treat nonunion fractures and related problems in bone healing, as a biological and physical method. With the use of Helmholtz coils and PEMF stimulators to generate uniform time-varying electromagnetic fields, the effects of extremely low frequency electromagnetic fields on bone mineral density (BMD) and local factor production in disuse osteoporosis (DOP) rats were investigated. Eighty 4-month-old female Sprague Dawley (SD) rats were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 27 publications
2
69
0
Order By: Relevance
“…PEMF involving a pulse train of 1, 10, 20, 40 Hz, and 1.5 mT in rats with STZ-induced diabetes had no effect on reduced body weight due to STZ but reduced blood glucose levels (14). Assessment of the effects of exposure of rats to 10-Hz square waves (1.8-3.8 mT) or 40 Hz sinusoidal (1.3-2.7 mT) magnetic fields on pancreatic structure and function showed that, after application for 14 days, glucose concentrations decreased in both groups, whereas insulin concentrations increased.…”
Section: Discussionmentioning
confidence: 85%
“…PEMF involving a pulse train of 1, 10, 20, 40 Hz, and 1.5 mT in rats with STZ-induced diabetes had no effect on reduced body weight due to STZ but reduced blood glucose levels (14). Assessment of the effects of exposure of rats to 10-Hz square waves (1.8-3.8 mT) or 40 Hz sinusoidal (1.3-2.7 mT) magnetic fields on pancreatic structure and function showed that, after application for 14 days, glucose concentrations decreased in both groups, whereas insulin concentrations increased.…”
Section: Discussionmentioning
confidence: 85%
“…This result suggests that the longer coil-sensor distance, the smaller the geometric difference in PEMF strength, particularly in terms of the uniformity of the stimulated area (i.e., a decrease in focality) at distances >40 mm. Testing the influence of PEMF stimulation on bone tissue in vivo [6,7,11], stimulation conditions with lower spatial focality would be preferable to achieve approximately equal PEMF strength throughout the whole marrow cavity with bone marrow in long bones. To the best of our knowledge, this is the first study investigating PEMF strength based on the measurements in marrow cavity in long bones under 810 stimulation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, stimulation intensity depends on stimulator output, distance and position [4,5]. Only a few in vivo studies have shown PEMF effects on bone formation processes in tissue, protein and mRNA levels [6][7][8]. An accompanying problem is the difficulty in determining magnetic field strength inside bone in vivo, as characterization of magnetic field strength in bone during PEMF stimulation under different conditions remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al / Effects of pulsed electromagnetic fields on histomorphometry and osteocalcin in DOP rats motion system damage. DOP is frequently seen in hemiplegia, fracture, long-term bed rest, and space flight [1,2]. In recent years, with the increase in the number older individuals and the use of mechanized transportation, the high incidence of disuse osteoporosis is becoming a significant problem in clinical medicine.…”
Section: S14mentioning
confidence: 99%
“…Disuse osteoporosis (DOP) is a kind of secondary osteoporosis that can be caused by various reasons, such as motion ability restriction or dysfunction or 1 These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%